Death in white pyjamas ; Death knows no calendar - Bude, John, 1901-1957 (Bude, John, 1901-1957. Superintendent William Meredith, 2020)
Death in white pyjamas: At the country home of Sam Richardson, a group of actors have gathered along with their somewhat sinister producer Basil Barnes, and a playwright whose star is rising in the drama scene. With competitive tension in the air between the three actresses, Clara, Angela and Deirdre, the spell is broken when Deirdre is found murdered in the grounds wearing, for some unknown reason, white pyjamas. Enter Inspector Hartin and Sergeant Dane to unravel this curious plot.